Exposure to Synthetic Gray Water Inhibits Amoeba Encystation and Alters Expression of Legionella pneumophila Virulence Genes - Buse, Helen Y. (Appl Environ Microbiol, 2015)
Water conservation efforts have focused on gray water (GW) usage, especially for applications that do not require potable water quality. However, there is a need to better understand environmental pathogens and their free-living amoeba (FLA) hosts within GW, given their growth potential in stored gray water. Using synthetic gray water (sGW) we examined three strains of the water-based pathogen Legionella pneumophila and its FLA hosts Acanthamoeba polyphaga, A. castellanii, and Vermamoeba vermiformis. Exposure to sGW for 72 h resulted in significant inhibition (P < 0.0001) of amoebal encystation versus control-treated cells, with the following percentages of cysts in sGW versus controls: A. polyphaga (0.6 versus 6%), A. castellanii (2 versus 62%), and V. vermiformis (1 versus 92%), suggesting sGW induced maintenance of the actively feeding trophozoite form. During sGW exposure, L. pneumophila culturability decreased as early as 5 h (1.3 to 2.9 log(10) CFU, P < 0.001) compared to controls (Δ0 to 0.1 log(10) CFU) with flow cytometric analysis revealing immediate changes in membrane permeability. Furthermore, reverse transcription-quantitative PCR was performed on total RNA isolated from L. pneumophila cells at 0 to 48 h after sGW incubation, and genes associated with virulence (gacA, lirR, csrA, pla, and sidF), the type IV secretion system (lvrB and lvrE), and metabolism (ccmF and lolA) were all shown to be differentially expressed. These results suggest that conditions within GW may promote interactions between water-based pathogens and FLA hosts, through amoebal encystment inhibition and alteration of bacterial gene expression, thus warranting further exploration into FLA and L. pneumophila behavior in GW systems.